The Development of Palliative Community Health Nursing to Increase Family’s Autonomy in Caring Patient with Cancer At Home - Elida Ulfiana; Eka Mishbahatul Mar’ah Has; Praba Diyan Rachmawati (Universitas Airlangga, 2013)
Introduction: Cancer still remains a disease with high mortality rate. Sustainable health services for cancer survivors are important to prevent relapse and improve patient’s quality of life. PCHN (Palliative Community Health Nursing) is a packet of community health nursing services given to the family and cancer’s patient at home, focused on promotive and preventive activities. The aim of this study was to analyze the influence of palliative community health nursing to increase family’s autonomy in caring patient with cancer at home.Method: This study was used pre-experiment design. The populations were family who lived with cancer’s patient post treatment. Samples were taken by purposive sampling technique; consist of 7 people. Variable independent was PCHN. Variable dependent were family’s autonomy in caring patient with cancer at home collected by using observation form. The data were then analyzed by using Wilcoxon Signed Rank Test, with α ≤ 0.05.Results: The results had showed the differences between family’s autonomy in caring patient at home before and after PCHN (p = 0.025).Discussion: PCHN can increase family’s autonomy in caring cancer’s patient at home. The implementation of PCHN through home visit can give informational support about cancer and treatment at home to the families. PCHN can be used as one of method to improve palliative services at community, in order to increase cancer’s patient quality of life. Further research, should develop PCHN which involve multidicipline team, such as health care provider, clergy, and health volunteer.